Turn-On Voltage Shift of Metal–Insulator–Oxide Semiconductor Thin-Film Diode by Adding Schottky Diode in Reverse Direction - Park, Jun-Woo; Lee, Donggun; Cho, Nam-Kwang; Lee, Jinwon; Kim, Youn Sang (ACS applied electronic materials, 2019)
Various efforts have been made to fabricate oxide thin-film diodes (TFDs) that will be applied to next-generation electronics to ensure thin, lightweight, and reliable operation. However, p–n-junction oxide TFDs are challenging to fabricate because of the absence of stable p-type oxide semiconductors, and metal–insulator–metal (MIM) diodes are inevitably subject to unnecessary power losses due to the high off-current induced by the thin insulator. Furthermore, the low rectification ratio and withstand voltage of MIM TFDs are also limits to overcome. Recently, a novel type of TFD with a metal–insulator–oxide semiconductor (MIOS) structure was reported. It shows a relatively high rectifying ratio, low off-current, and a stable withstand voltage. However, finding a way to shift the diode’s turn-on voltage for various specifications and applications of MIOS TFDs remains a challenge. Herein, we propose a novel approach to shift the turn-on voltage of MIOS TFDs. By adding a metal electrode to the oxide semiconductor, different shifts of the turn-on voltage of MIOS TFDs could be realized depending on the characteristic variation of the Schottky contact between the metal electrode and the oxide semiconductor. ZnO/Ag-based TFD shifted to 4.0 V because of the reverse Schottky diode formed on the oxide semiconductor. a-IGZO/Au-based TFD showed a turn-on voltage of 8.4 V. a-IGZO + AgO X /Ag-based TFD turned on at 12.8 V because of the enhanced Schottky property. These findings are expected to help develop diverse MIOS TFDs and expand their capabilities in the future.